Peran Profitabilitas dalam Memediasi Pengaruh Ukuran Perusahaan terhadap Nilai Perusahaan Kesehatan - WILLIAM VALENTINO RICARD; Anton Arisman (MDP Student Conference, 2026)
This study aims to examine the effect of firm size on firm value withprofitability as a mediating variable in healthcare sector companies listed onthe Indonesia Stock Exchange (IDX). The study employs secondary dataobtained from the annual financial statements of healthcare companies duringthe 2023–2024 period. Firm size is proxied by total assets, profitability ismeasured using Return on Assets (ROA), and firm value is measured using Priceto Book Value (PBV). Data analysis is conducted using multiple linearregression and mediation testing with a causal step approach, utilizing SPSSsoftware.The results indicate that firm size does not have a positive effect on profitability,leading to the rejection of the first hypothesis. However, firm size andprofitability are each proven to have a positive effect on firm value.Furthermore, profitability is found to partially mediate the relationship betweenfirm size and firm value, as the direct effect of firm size on firm value remainssignificant after the mediating variable is included in the model.